Patient perceptions of communication with diagnostic radiographers. Issue 4 (November 2019) - Pollard, N.; Lincoln, M.; Nisbet, G.; Penman, M.
Abstract: Introduction: The aims of this study were to (1) examine what makes a communication encounter with a diagnostic radiographer effective from the patient's perspective and (2) explore the impact of communication skills on the relationship between a diagnostic radiographer and their patient. Methods: Semi-structured interviews were conducted with 10 patients immediately after their imaging examination. Completed interviews were analysed using an inductive approach. Results: Five themes were identified in the qualitative data. (1) Introduction and Greeting, (2) Explanation/Instruction, (3) Feeling at ease, (4) Clear communication and (5) Gentle manner. Conclusion: These results have identified that effective communication promotes the development of rapport and trust between the radiographer and patient. These findings have implications for practitioners, educators and university programs and should be considered in the development of communication skills training programs for diagnostic radiography students. Highlights: Effective communication between a radiographer and patient helps the patient feel confident, comfortable and at ease. Clear explanation to the patient about the procedure and what is going to happen promotes confidence. Radiographers who attended to patients' physical and psychological comfort were viewed as effective communicators. Effective communication facilitates confidence in the radiographers' ability. Effective communication facilitates confidence that the imaging results will be accurate.